Rhetorical structures and cyclical patterns in forestry research articles - Nasirizadeh, Zahra; Paramasivam, Shamala; Nimehchisalem, Vahid; Omar, Noritah (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2022)
There have been a considerable number of studies on the research article genre (RA) from different perspectives of form and function. However, limited studies have examined the overall organizational structure of articles with all the main sections of the research article, Introduction-Methods-Results-Discussion (IMRD). There are also variations in the IMRD sections of the research article across different disciplines. The present study sought to analyze a) the rhetorical structure of individual sections of Forestry RAs in ISI journals, and b) analyze the cyclical patterns appearing in each section. A corpus of 40 research articles from five ISI journals were selected for this study. The selected articles were extracted from high impact factor journals in Forestry. The corpus was analysed based on Kanoksilapatham (2005) model as the analytical tool to explore the rhetorical moves in the corpus. Analysis of the research articles revealed that all sections did not follow the same rhetorical structure as specified in Kanoksilapatham (2005) model. On the basis of the analysis, some new moves or steps were realized. In terms of cyclical patterns, the findings pointed to the pervasiveness of salient move cycles in each section. Awareness of the rhetorical structure of RAs functions as an avenue to empower scholars, particularly novice writers, to integrate robustly into the academic community of their discipline.